2014
DOI: 10.1007/s10825-014-0596-6
|View full text |Cite
|
Sign up to set email alerts
|

Gate-modulated graphene quantum point contact device for DNA sensing

Abstract: In this paper, we present a computational model to describe the electrical response of a constricted graphene nanoribbon (GNR) to biomolecules translocating through a nanopore. For this purpose, we use a self-consistent 3D Poisson equation solver coupled with an accurate three-orbital tight-binding model to assess the ability for a gate electrode to modulate both the carrier concentration as well as the conductance in the GNR. We also investigate the role of electrolytic screening on the sensitivity of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…In the present study, limited though by small sampling, conductance variations are indistinguishable for poly(A-T) 15 and poly(G-C) 15 cases. The general trend in conductance does not change when the molarity is changed from 1 M to 0.1 M. However, the magnitude of conductance variations is suppressed for the low molarity case, e.g., conductance variation for B-DNA (A in Figure 6) reduces from 10 μ S to 2 μ S for a change in molar concentration from 1 M to 0.1 M. In the low molarity case, due to reduced screening, the average potential induced on the graphene membrane is much larger in magnitude compared to the high molarity case (see Supplementary Figures S7 and S8), which is equivalent to a gating effect and changes the bias point of the QPC significantly [48]. Although reduced screening, at low molar concentrations, increases the magnitude of the potential induced at the pore mouth, the variation in conductance itself is not enhanced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, limited though by small sampling, conductance variations are indistinguishable for poly(A-T) 15 and poly(G-C) 15 cases. The general trend in conductance does not change when the molarity is changed from 1 M to 0.1 M. However, the magnitude of conductance variations is suppressed for the low molarity case, e.g., conductance variation for B-DNA (A in Figure 6) reduces from 10 μ S to 2 μ S for a change in molar concentration from 1 M to 0.1 M. In the low molarity case, due to reduced screening, the average potential induced on the graphene membrane is much larger in magnitude compared to the high molarity case (see Supplementary Figures S7 and S8), which is equivalent to a gating effect and changes the bias point of the QPC significantly [48]. Although reduced screening, at low molar concentrations, increases the magnitude of the potential induced at the pore mouth, the variation in conductance itself is not enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…The change in the electrostatic potential around the nanopore mouth is < 5%, when the surface charge density changes from 10 21 /cm 3 to 10 10 /cm 3 [8], and ignoring the effect of surface charges is justified. In addition, a gate electrode can be used to adjust the carrier concentration and, thereby, offset the effects of the surface charge on the transverse electronic conductance [48]. …”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We take f ( E ) as the Fermi-Dirac distribution function and the temperature as 295 K. The Fermi energy E F is set equal to μ 1 . In practice, E F can be adjusted by an external gate bias as proposed in a previous work [22]. In this analysis, it is taken to be an external parameter without any loss of generality.…”
Section: Methodsmentioning
confidence: 99%
“…(Nelson et al 2010) considered a semiconducting aGNR channel with a nanopore and claimed that the larger purine G and A will produce higher conductance than smaller pyrimidine C and T. It was also suggested that such a device configuration gives the possibility of orientation-independent sequencing. While the presence of a nanopore reduces the conductance of the GNR electrode, it was also suggested that shaping the nanoribbon geometry with the lateral constriction integrated with the motion of charged group and screening depending on electrical gate or external charge could enhance the sensitivity of the DNA sequencer (Girdhar et al 2013(Girdhar et al , 2014.…”
Section: Graphene Nanopore (Mode Ii-b)mentioning
confidence: 99%